Stable and efficient Sb2Se3 solar cells with solution-processed NiOx hole-transport layer. (April 2021) - Guo, Liping; Vijayaraghavan, S.N.; Duan, Xiaomeng; Menon, Harigovind G.; Wall, Jacob; Kong, Lingyan; Gupta, Subhadra; Li, Lin; Yan, Feng
Graphical abstract: Highlights: Low cost and stable solution-processed inorganic NiOx hole transport layer for Sb2 Se3 solar cells. Close space sublimation deposition of the Sb2 Se3 absorber material. Sb2 Se3 with NiOx hole transport layer achieve a power conversion efficiency 7.3%. The stability of the Sb2 Se3 solar cells with NiOx hole transport layer can be improved. Abstract: Sb2 Se3 is a promising absorber material for thin-film solar cells owing to its earth-abundant and non-toxic constituents, superior optoelectronic properties, and unique one-dimensional crystal structure. To further increase the power conversion efficiency of the Sb2 Se3, we fabricated an n-i-p structure by integrating a solution-processed NiOx hole-transport layer (HTL) into Sb2 Se3 solar cells to enhance the carrier collection. In this study, we systematically screen the thickness of NiOx HTL and demonstrate an improved average power conversion efficiency from 6.12% to 7.15% with a 50 nm NiOx HTL. The mechanism associated with the improved device performance was characterized through the microstructure of the material, device physics, and interface electronic behaviors. It is also shown that the low-cost and scalable solution-processed NiOx HTL can improve device stability under an accelerated stress test. Thus, this work paves a way to further improve the performance of antimony chalcogenides-based solar cells via tailoring the inorganic HTL.